Pengaruh Transaksi C2c Commerce terhadap Perilaku Impulsive Buying (Servei pada Konsumen PT Shopee International Indonesia) - Siti Maryam; Sri Wahyuningsih (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2018)
This research is motivated by of business competition which utilize internet media as place of marketing communication. This study aims to determine how big influence of C2C Commerce transaction to impulsive buying behavior. The theory used in this research is theory of integrated marketing communication (IMC) with elements that support the interactive/internet marketing and consumer behavior that enter the theory of communication behavior. This research methodology uses quantitative approach and it kind of eksplanatif research. This study has a population of 46,640 people with a sample of 100 respondents using the Yamane formula. The test results obtained correlation test of 0.765 which means have a strong relationship, and coefisisen determination magnitude 66% and the remaining 34%. While the value of T arithmetic of 11.757> from T table of 1.660. Which means that C2C Commerce Transactions (variable x) has influence to the behavior of Impulsive Buying. The conclusion of this research is C2C Commerce Transaction can attract consumers because of the various kinds of transaction convenience offered by C2C Commerce model, thus forming impulsive buying behavior to the consumer. The Suggestions in this research is, It is also necessary for Shopee to improve the quality of service and continue to innovate in satisfying the consumer.